Surgical management of recurrent cervical sialoceles in four dogs. (4th March 2013) - Tsioli, V.; Papazoglou, L.G.; Basdani, E.; Kosmas, P.; Brellou, G.; Poutahidis, T.; Bagias, S.
Abstract : Recurrent cervical sialoceles were diagnosed in four dogs associated with inadequate excision of the sublingual gland. Three dogs were managed by resection of the remnants of the sublingual gland via an oral approach. One dog was managed through a ventral approach as identification of the sublingual gland was not possible with the oral approach. The outcome was favourable in all cases and no relapses were detected after a median follow‐up time of 10 months.